Simulated analog crayfish meat based on 3D print: Effect of crayfish oil emulsion on gel properties of surimi - Xiaofeng Zhan; Shuhui Yang; Weixia Zhou; Yanyan Wang; Jianhua Rong; Youming Liu; Chuan Li; Yongqiang Zhao; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Spon2 knockdown suppresses the phenotype of house dust mite-induced allergic asthma in mice and cells - Haihan Zheng; Shenggang Ding; Daoxiang Rong; Ting Li; Mei Xiong (Immunologic Research, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Effects of EGCG/TGase on the physicochemical properties and in vitro dynamic digestion characteristics of water-saving rinsed surimi gels - Qin Yang; Weixia Zhou; Die Hu; Chuan Li; Lu Zhang; Yongqiang Zhao; Shengbi Zou; Ru Liu; Youming Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Insights into the synergistic cross-linking effect of EGCG and TGase on surimi gels - Qin Yang; Jinling Li; Wentao Ma; Ru Liu; Shengbi Zou; Yongqiang Zhao; Shanbai Xiong; Jianhua Rong; Yang Hu (Food Chemistry, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

A sliding window method considering image shadow to detect Mars rock from MRO HiRISE datasets - Na Sun; Yongjiu Feng; Xiaohua Tong; Pengshuo Li; Rong Wang; Yuhao Wang; Yuze Cao; Zilong Cao; Xiong Xu; Yusheng Xu; Shijie Liu (Planetary and Space Science, 2025)

The application of manure and straw is beneficial for improving the content and stability of DOM in paddy soil - Qinghua Zhou; Jiayue Zhou; Weiliang Xiong; Shiwei Li; Ouping Deng; Yi Xiao; Xingyu Li; Bing Li; Changquan Wang; Xuesong Gao; Genchuan Bai; Jiang Liu; et al. (Journal of Environmental Management, 2025)

Unraveling the source-terminal PAH pollution from coal chemical wastewater in the Yellow River Basin via molecular fingerprint concentration analysis - Rong Li; Quanzhen Liu; Xiong Xu; Yongchang Xie; Lihua Lin; Mengru Yang; Donghong Wang (Environmental Pollution, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Enhancing vessel trajectory prediction with bi-state space and squeeze excitation attention - Caiquan Xiong; Jiaming Li; Xinyun Wu; Donghua Liu; Qi Wang; Rong Gao; Jinjia Ruan (Ocean Engineering, 2025)

Spatiotemporal analysis of microclimatic and environmental interactions with visualcompensation for thermalcomfort: Case studies in Hangzhou's urban waterfronts - Rong Xia; Zhixing Li; Xiaowen Gao; Siyi Luo; Ruiyin Xiong; Xuzhong Yan (Urban Climate, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Organic fertilizer intensifies the vertical heterogeneity of DOM in paddy fields through interactions with soil minerals - Yi Xiao; Rong Huang; Weiliang Xiong; Binbin Liu; Qinghua Zhou; Tao Jiang; Vanessa N.L. Wong; Jiang Liu; Yingjie Wu; Youlin Luo; Qiquan Li; Qiang Xu; et al. (Soil and Tillage Research, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Monitoring-based analysis of the responses of upper structure and tunnel lining during shield tunneling with pile cutting - Zhi-Xiong Liu; Xiao-Wei Ye; Ke Song; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Large-scale crop dataset and deep learning-based multi-modal fusion framework for more accurate G × E genomic prediction - Qixiang Zou; Shuaishuai Tai; Qianguang Yuan; Yating Nie; Heping Gou; Longfei Wang; Chuanxiu Li; Yi Jing; Fangchun Dong; Zhen Yue; Yi Rong; Xiaodong Fang; et al. (Computers and Electronics in Agriculture, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

Vitamin C alleviates intestinal damage induced by 17α-methyltestosterone in Carassius auratus - Haiyan Zhao; Tongyao Li; Chenyang Li; Zijun Xiong; Weiya Rong; Lu Cao; Gen Chen; Qing Liu; Yu Liu; Xianzong Wang; Shaozhen Liu (Aquatic Toxicology, 2025)

Integrating larval zebrafish model and network pharmacology for screening and identification of edible herbs with therapeutic potential for MAFLD: A promising drug Smilax glabra Roxb. - Yinjuan Xiong; Xixuan Huang; Yuxin Li; Yukang Nie; Haodong Yu; Yaqi Shi; Jiajie Xue; Zhehui Ji; Keming Rong; Xuezhen Zhang (Food Chemistry, 2025)

Effects of exposure to 17α-methyltestosterone on hepatic lipid metabolism in Gobiocypris rarus - Tongyao Li; Zijun Xiong; Weiya Rong; Qiong Yang; Yue Chen; Haiyan Zhao; Qing Liu; Jing Song; Weiwei Wang; Yu Liu; Xianzong Wang; Shaozhen Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Research on an adaptive prediction method for restaurant air quality based on occupancy detection - Yu Zhao; Chang Xiong; Li Rong; Zhiwen Luo; Tareq Hussein; Tianyi Zhao (Building and Environment, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.